2011
DOI: 10.1016/j.ijrobp.2010.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Regulates Low-Linear Energy Transfer γ-Radiation-Induced NFκB-Dependent Telomerase Activity in Human Neuroblastoma Cells

Abstract: Purpose-We recently reported that curcumin attenuates radiation (IR) induced survival signaling and proliferation in human neuroblastoma (NB) cells. Also, in endothelial system, we demonstrated that NFκB regulates IR-induced telomerase activity (TA). Accordingly, we investigated the effect of curcumin in inhibiting IR-induced NFκB dependent hTERT transcription, TA and cell survival in NB cells.Methods and Materials-SK-N-MC or SH-SY5Y cells exposed to IR, treated with curcumin (10nM-100nM) with or without IR we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Many recently studies show that the telomerase involved in the progress of the DNA DSB repair. And several studies also supports that the telomerase activity and the telomere status have impacts on the response to ionizing radiation (Aravindan et al, 2011). Current literature indicates that telomerase has a radiationinducible function lead to resistance of cells to irradiation.…”
Section: Discussionmentioning
confidence: 89%
“…Many recently studies show that the telomerase involved in the progress of the DNA DSB repair. And several studies also supports that the telomerase activity and the telomere status have impacts on the response to ionizing radiation (Aravindan et al, 2011). Current literature indicates that telomerase has a radiationinducible function lead to resistance of cells to irradiation.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, we dissected out that IR induced NFκB in human NB cells [14,15] is responsible for the induced TERT transcription, enhanced TA and subsequent clonal expansion [16]. In this context, clearly, there is a need to recognize new, effective and clinical-translation feasible drugs that selectively target radiation induced NFκB-dependent TERT to mitigate clonal expansion and NB progression.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, clearly, there is a need to recognize new, effective and clinical-translation feasible drugs that selectively target radiation induced NFκB-dependent TERT to mitigate clonal expansion and NB progression. Concurrently, we have shown that curcumin (diferuloylmethane), a polyphenol, sensitizes NB cells to the apoptotic effects of radiation [14] and, further mitigates radiation-induced NFκB-dependent TERT transcription, TA and subsequent clonal expansion [16]. However, the full potential of curcumin has not been realized because of the relatively poor bioavailability in the clinical settings [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has suggested that IR-induced NFκB in surviving tumor cells is a critical determinant of overall response to RT (5, 6, 14) and further demonstrated that selectively targeting IR-induced NFκB alleviated radiation resistance in many tumor models (8, 9, 11, 17-19). Therefore, targeting the NFκB pathway involved in the secretion of radiation-responsive factors such as SOD2, cMYC, IL-1α or TNF-α may prove a promising strategy to mitigate IR-induced radiation protection.…”
Section: Discussionmentioning
confidence: 96%